Ni‐Catalyzed C−F Bond Functionalization of Unactivated Aryl Fluorides and Corresponding Coupling with Oxazoles. Issue 8 (9th March 2018) - Yin, Youzhi; Yue, Xiaoyu; Zhong, Qi; Jiang, Hanmin; Bai, Ruopeng; Lan, Yu; Zhang, Hua
Abstract: A Ni‐catalyzed C−F bond functionalization of unactivated aryl fluorides with oxazoles as coupling partners was developed. Various arylated oxazoles could be obtained in moderate to good yields in the presence of Ni(cod)2 /IMes catalytic system. A rapid synthesis of natural product texaline was also demonstrated using this protocol. This transformation could be potentially utilized in regioselective introduction of an oxazole group in late‐stage synthetic applications. Abstract :